UTILIZATION OF INFORMATION ON DAIRYING AMONG TRIBAL AND NON-TRIBAL DAIRY FARMERS IN CACHAR DISTRICT OF ASSAM* (Indian Journal of Animal Production and Management, 2014)
The study was done in the 4 development blocks having relatively higher intensity of mix population of tribal and non-tribal farmers in Cachar district of Assam. Altogether 100 randomly selected dairy farmers were considered as respondents. Majority belonged to medium level of extent of utilization of information related to dairying in both tribal and non tribal dairy farmers. There existed significant difference in utilizing the information sources between the tribal and non-tribal farmers with non-tribal farmers scoring higher means. Veterinary officials, relatives and friends were mostly the key sources for utilization of dairying information in case of both tribal and non-tribal dairy farmers.
Keywords: Utilization of information; dairying; tribal and non-tribal farmer